Tris(pentafluorophenyl)borane‐Catalyzed Carbenium Ion Generation and Autocatalytic Pyrazole Synthesis—A Computational and Experimental Study. Issue 46 (12th October 2021) - Dasgupta, Ayan; Babaahmadi, Rasool; Pahar, Sanjukta; Stefkova, Katarina; Gierlichs, Lukas; Yates, Brian F.; Ariafard, Alireza; Melen, Rebecca L.
Abstract: In recent years, metal‐free organic synthesis using triarylboranes as catalysts has become a prevalent research area. Herein we report a comprehensive computational and experimental study for the highly selective synthesis of N‐substituted pyrazoles through the generation of carbenium species from the reaction between aryl esters and vinyl diazoacetates in the presence of catalytic tris(pentafluorophenyl)borane [B(C6 F5 )3 ]. DFT studies were undertaken to illuminate the reaction mechanism revealing that the in situ generation of a carbenium species acts as an autocatalyst to prompt the regiospecific formation of N‐substituted pyrazoles in good to excellent yields (up to 81 %). Abstract : Tris(pentafluorophenyl)borane‐catalyzed reactions between vinyl diazoacetates and aryl esters afforded highly regioselective N‐alkylated pyrazoles. These reactions involve an autocatalytic process in which in situ formed carbenium species act as a catalyst to regioselectively afford pyrazoles. Detailed DFT studies were carried out to explain the reaction mechanism.